EVIDENCE FOR DECISIONS IN THE TIME OF COVID-19: Eyes on Africa - Nasreen Jessani; Laurenz Langer; Carina van Rooyen; Ruth Stewart (The Thinker)
As Covid-19 sweeps across the globe, one of the biggest questions in many minds is ‘how will this crisis affect Africa?’ (Nyenswah, 2020; Pillay, 2020; Wood, 2020; World Bank, 2020a). Fears abound that the pandemic will multiply and deepen existing socio-economic issues, such as high levels of unemployment, poverty, and inequality.